2022
DOI: 10.1302/2633-1462.311.bjo-2022-0125.r1
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence-generated hip radiological measurements are fast and adequate for reliable assessment of hip dysplasia

Abstract: Aims Hip dysplasia (HD) leads to premature osteoarthritis. Timely detection and correction of HD has been shown to improve pain, functional status, and hip longevity. Several time-consuming radiological measurements are currently used to confirm HD. An artificial intelligence (AI) software named HIPPO automatically locates anatomical landmarks on anteroposterior pelvis radiographs and performs the needed measurements. The primary aim of this study was to assess the reliability of this tool as compared to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“… 42 Regarding congenital abnormalities, such as hip dysplasia, studies have also shown practicalities for radiological measurements in a quick and effective manner. 44 AI-assisted diagnosis and classification of OA from radiographs have demonstrated similar accuracy to senior clinicians. 20 Furthermore, CNNs for osteoporosis fracture recognition have been developed to directly evaluate bone mineral density from radiographs.…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 91%
“… 42 Regarding congenital abnormalities, such as hip dysplasia, studies have also shown practicalities for radiological measurements in a quick and effective manner. 44 AI-assisted diagnosis and classification of OA from radiographs have demonstrated similar accuracy to senior clinicians. 20 Furthermore, CNNs for osteoporosis fracture recognition have been developed to directly evaluate bone mineral density from radiographs.…”
Section: Image Recognition and Diagnosticsmentioning
confidence: 91%
“…The clearer, enhanced AI imaging produced by the CNN model led to a diagnosis that was consistent with intraoperative findings. Regarding congenital abnormalities, such as hip dysplasia, studies have also shown practicalities for radiological measurements in a quick and effective manner [17]. AI-assisted diagnosis and classification of OA from radiographs have demonstrated similar accuracy to senior clinicians [18].…”
Section: Ai and Orthopaedic Surgerymentioning
confidence: 99%
“…Machine learning algorithms can analyze medical imaging to detect and classify various orthopaedic conditions, including fractures, tumours, and joint abnormalities. 2 , 3 AI algorithms can assist in identifying subtle patterns or anomalies that might be missed by human observers, leading to earlier detection and treatment.…”
Section: Diagnostic Assistancementioning
confidence: 99%